Allele-specific silencing of a dominant SETX mutation in familial amyotrophic lateral sclerosis type 4 - Audrey Winkelsas; Athena Apfel; Brian Johnson; George Harmison; Kimberly Diaz Perez; Dongjun Li; Vivian G. Cheung; Christopher Grunseich (HGG Advances)
Summary: Amyotrophic lateral sclerosis 4 (ALS4) is an autosomal dominant motor neuron disease that is molecularly characterized by reduced R-loop levels and caused by pathogenic variants in senataxin (SETX). SETX encodes an RNA/DNA helicase that resolves three-stranded nucleic acid structures called R-loops. Currently, there are no disease-modifying therapies available for ALS4. Given that SETX is haplosufficient, removing the product of the mutated allele presents a potential therapeutic strategy. We designed a series of siRNAs to selectively target the RNA transcript from the ALS4 allele containing the c.1166T>C mutation (p.Leu389Ser). Transfection of HEK293 cells with siRNA and plasmids encoding either wild-type or mutant (Leu389Ser) epitope-tagged SETX revealed that three siRNAs specifically reduced mutant SETX protein levels while having minimal effect on the wild-type SETX protein. In ALS4 primary fibroblasts, siRNA treatment silenced the endogenous mutant SETX allele while sparing the wild-type allele and restored R-loop levels in patient cells. Our findings demonstrate that mutant SETX, differing from wild-type by a single nucleotide, can be effectively and specifically silenced by RNA interference.